Digital Literacy as a Mediator Between Digital Finance Adoption and Financial Inclusion Among SMEs in Oyo State, Nigeria - Sajuyigbe, Ademola Samuel; Obi, Nwoye James; Oladapo, John Tawiah; Adegun, Emmanuel Aderinola; Adedoyin, Adewumi Ramat; Dunsin, Abimbola Tolulope (Universitas Airlangga, 2025)
The study investigates the mediating role of digital literacy in the relationship between digital finance and financial inclusion among SMEs in Oyo State, Nigeria. Data were collected through a questionnaire administered to 298 SME CEOs across the Agro-allied, Manufacturing, Education, and Construction sectors. Path Analysis Structural Equation Modelling (PA-SEM) was employed as the primary analytical technique. Findings reveal that digital finance significantly enhances financial inclusion, while digital literacy also exerts a strong positive influence on financial inclusion. Furthermore, the analysis shows that digital literacy partially mediates the relationship between digital finance and financial inclusion, as confirmed through bootstrapping. This highlights the critical role of digital literacy in amplifying the benefits of digital finance for financial inclusion. The results suggest that SMEs with higher digital literacy levels are better equipped to utilize digital finance tools, such as mobile money, online banking, and payment platforms, thereby achieving greater financial inclusion. Consequently, it is recommended that SMEs prioritize developing the digital skills of their operators and employees to maximize the advantages offered by digital finance solutions.